2016
DOI: 10.1056/nejmoa1510491
|View full text |Cite
|
Sign up to set email alerts
|

Kidney-Failure Risk Projection for the Living Kidney-Donor Candidate

Abstract: Background Evaluation of candidates for living kidney donation relies on screening for individual risk factors for end-stage renal disease (ESRD). To support an empirical approach to donor selection, we developed a tool that simultaneously incorporates multiple health characteristics to estimate a person’s likely long-term risk of ESRD in the absence of donation. Methods We used meta-analyzed risk associations from 7 general population cohorts, calibrated to US population-level incidence of ESRD and mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
379
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 378 publications
(402 citation statements)
references
References 32 publications
(44 reference statements)
7
379
1
8
Order By: Relevance
“…[12] The latter results were recently used as a reference level in a model predicting the lifetime risk of RRT in people who were potential kidney donors, but did not donate a kidney. [2] As the lifetime risk in the European general population is substantially lower than in the USA, the reference level in potential living kidney donors is also likely to be lower. Consequently, the risk prediction model that was developed by the CKD Prognosis Consortium for people in the USA, Canada and Israel needs to be recalibrated and validated before implementation in Europe.…”
Section: Relation To Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[12] The latter results were recently used as a reference level in a model predicting the lifetime risk of RRT in people who were potential kidney donors, but did not donate a kidney. [2] As the lifetime risk in the European general population is substantially lower than in the USA, the reference level in potential living kidney donors is also likely to be lower. Consequently, the risk prediction model that was developed by the CKD Prognosis Consortium for people in the USA, Canada and Israel needs to be recalibrated and validated before implementation in Europe.…”
Section: Relation To Other Studiesmentioning
confidence: 99%
“…Recently the Chronic Kidney Disease (CKD) Prognosis Consortium published such a risk prediction model for the lifetime risk of ESRD in potential kidney donors. [2] This model was based on populations from Canada, the USA and Israel, [2,3] and may not be generalizable to European populations. For example, the incidence of renal replacement therapy (RRT), defined as haemodialysis, peritoneal dialysis and kidney transplantation, in the United States is almost two times higher than that of Belgium and Greece, both countries with the highest incidence of RRT in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…14 Hypertension is present in 30% of the general population, and the prevalence increases with age; some studies report that it is present in 2% of living donors at the time of donation (we observed a rate of 5%) and develops in up to 40% of donors over time. 15,16 Garg and associates reported a 10-year hypertension rate of 16% postdonation, about 5% higher than in the control population. 16 The literature suggests that transplant programs generally exclude donors with a BMI > 35 kg/m², and 10% of programs exclude donors with a BMI > 30 kg/m².…”
Section: Discussionmentioning
confidence: 96%
“…"nd on what basis does the center make its decision other than personal feeling of the selection team. Grams et al [18] have recently created a model that can help to predict the risk of eventual renal failure in potential kidney donors. "ut there will always be some uncertainty in donor selection.…”
Section: Living Donorsmentioning
confidence: 99%